Application of Thruster Fault-Tolerant Control System based on the Hybrid Method for Control Allocation in Real-World Environment. Issue 21 (2019) - Omerdic, Edin; Toal, Daniel; Dooly, Gerard
Abstract: Fault-tolerant control system for marine robots, developed by researchers at Centre for Robotics & Intelligent Systems (CRIS), University of Limerick, utilises the hybrid method for control allocation, based on the integration of the pseudoinverse and the fixed-point iteration method. The algorithm is implemented as a two-step process. In the first step, the pseudoinverse solution is found, and the feasibility of the solution is examined analysing its components. If violation of actuator constraint(s) is detected, the fixed-point iteration method is activated in the second step. In this way, the hybrid method for control allocation can allocate the exact solution, optimal in the l2 sense, inside the entire attainable command set. This solution minimises a control energy cost function, the most suitable criteria for underwater applications. The performance of the thruster fault-tolerant control system has been validated during the research cruise CE19001, where the work-class ROV Étaín, deployed from support vessel Celtic Explorer via Tether Management System (TMS), successfully performed several complex subsea tasks with a faulty horizontal thruster. This paper describes the algorithm, provides geometric interpretation and presents the results from field trials.